\(\frac{5\sqrt{5}+3\sqrt{3}}{\sqrt{3}+\sqrt{5}}\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

14 tháng 8 2016

E=\(\frac{\left(\sqrt{5}\right)^3+\left(\sqrt{3}\right)^3}{\sqrt{5}+\sqrt{3}}=\frac{\left(\sqrt{5}+\sqrt{3}\right)\left(5-\sqrt{15}+3\right)}{\sqrt{5}+\sqrt{3}}\)=8-\(\sqrt{15}\)

14 tháng 8 2016

\(\frac{5\sqrt{5}+3\sqrt{3}}{\sqrt{3}+\sqrt{5}}=8-\sqrt{15}\)nha avt745471_60by60.jpg hoshi nguyen                    ^_^

10 tháng 8 2016

\(=\sqrt{\frac{\left(3+\sqrt{5}\right)\left(3+\sqrt{5}\right)}{\left(3-\sqrt{5}\right)\left(3+\sqrt{5}\right)}}+\sqrt{\frac{\left(3-\sqrt{5}\right)\left(3-\sqrt{5}\right)}{\left(3+\sqrt{5}\right)\left(3-\sqrt{5}\right)}}\)

\(=\frac{3+\sqrt{5}}{\sqrt{9-5}}+\frac{3-\sqrt{5}}{\sqrt{9-5}}=3\)

16 tháng 7 2019

\(A=\frac{1}{\sqrt{3}+1}+\frac{1}{\sqrt{3}-1}\)

\(=\frac{\sqrt{3}-1}{\left(\sqrt{3}+1\right)\left(\sqrt{3}-1\right)}+\frac{\sqrt{3}+1}{\left(\sqrt{3}-1\right)\left(\sqrt{3}+1\right)}\)

\(=\frac{\sqrt{3}-1+\sqrt{3}+1}{\left(\sqrt{3}+1\right)\left(\sqrt{3}-1\right)}\)

\(=\frac{2\sqrt{3}}{\left(\sqrt{3}+1\right)\left(\sqrt{3}-1\right)}\)

\(=\frac{2\sqrt{3}}{3-1}\)

\(=\frac{2\sqrt{3}}{2}\)

\(=\sqrt{3}\)

\(B=\frac{5+\sqrt{5}}{5-\sqrt{5}}+\frac{5-\sqrt{5}}{5+\sqrt{5}}\)

\(=\frac{\sqrt{5}\left(\sqrt{5}+1\right)}{\sqrt{5}\left(\sqrt{5}-1\right)}+\frac{\sqrt{5}\left(\sqrt{5}-1\right)}{\sqrt{5}\left(\sqrt{5}+1\right)}\)

\(=\frac{\left(\sqrt{5}+1\right)}{\left(\sqrt{5}-1\right)}+\frac{\left(\sqrt{5}-1\right)}{\left(\sqrt{5}+1\right)}\)

\(=\frac{\left(\sqrt{5}+1\right)^2}{\left(\sqrt{5}-1\right)\left(\sqrt{5}+1\right)}+\frac{\left(\sqrt{5}-1\right)^2}{\left(\sqrt{5}+1\right)\left(\sqrt{5}-1\right)}\)

\(=\frac{5+2\sqrt{5}+1+5-2\sqrt{5}+1}{\left(\sqrt{5}-1\right)\left(\sqrt{5}+1\right)}\)

\(=\frac{12}{\left(\sqrt{5}-1\right)\left(\sqrt{5}+1\right)}\)

\(=\frac{12}{5-1}\)

\(=\frac{12}{4}\)

\(=3\)

20 tháng 7 2016

\(\frac{\sqrt{9-4\sqrt{5}}}{2-\sqrt{5}}\)

\(\frac{\sqrt{2^2-2\sqrt{5}2+\sqrt{5^2}}}{2-\sqrt{5}}\)

\(\frac{\sqrt{\left(2-\sqrt{5}\right)^2}}{2-\sqrt{5}}\)

\(\frac{\sqrt{5}-2}{2-\sqrt{5}}\)

= -1

Chúc bạn làm bài tốt :)

26 tháng 12 2016

=\(\frac{\left(\sqrt{5}-2\sqrt{3}\right)\left(\sqrt{5}-\sqrt{3}\right)-\left(2\sqrt{5}+\sqrt{3}\right)\left(\sqrt{5}+\sqrt{3}\right)}{\left(\sqrt{5}+\sqrt{3}\right)\left(\sqrt{5}-\sqrt{3}\right)}\)

=\(\frac{5-\sqrt{15}-2\sqrt{15}+6-10-2\sqrt{15}-\sqrt{15}-3}{5-3}\)

\(=\frac{-2-6\sqrt{15}}{2}=\frac{-2\left(1+3\sqrt{15}\right)}{3}=-1-3\sqrt{15}\)

a: \(=-6\sqrt{b}-\dfrac{1}{3}\cdot3\sqrt{3b}+\dfrac{1}{5}\cdot5\sqrt{6b}\)

\(=-6\sqrt{b}-\sqrt{3}\cdot\sqrt{b}+\sqrt{6}\cdot\sqrt{b}\)

\(=\sqrt{b}\left(-6-\sqrt{3}+\sqrt{6}\right)\)

c: \(=\sqrt{\left(5+2\sqrt{6}\right)^2}+\sqrt{\left(5-2\sqrt{6}\right)^2}\)

\(=5+2\sqrt{6}+5-2\sqrt{6}=10\)

d: \(A=\sqrt{\sqrt{5}-\sqrt{3-2\sqrt{5}+3}}\)

\(=\sqrt{\sqrt{5}-\sqrt{6-2\sqrt{5}}}\)

\(=\sqrt{\sqrt{5}-\sqrt{5}+1}=1\)

e: \(B=\sqrt{6+2\sqrt{5-2\sqrt{3}-1}}\)

\(=\sqrt{6+2\cdot\left(\sqrt{3}-1\right)}=\sqrt{4+2\sqrt{3}}=\sqrt{3}+1\)